FOREIGN COUNTRIES' EXPERIENCE IN ENSURING AND ASSESSING THE SOLVENCY OF INSURANCE ORGANIZATIONS (American Journal of Business Management, Economics and Banking, 2026)
This article presents an analysis of the experience of foreign countries in ensuring and assessing the solvency of insurance organizations. In addition, proposals and practical recommendations aimed at the experience of foreign countries in ensuring and assessing the solvency of insurance organizations have been developed.